2022
DOI: 10.1097/gox.0000000000004237
|View full text |Cite
|
Sign up to set email alerts
|

A Study of a Novel Controlled Focal Septa Release Method for Improving Cellulite

Abstract: Background: Cellulite is a common and often emotionally distressing condition among affected individuals. The dimpled appearance is caused by fibrous connective tissue, or septa, which tether the dermis to underlying fascia. A novel, minimally invasive, controlled focal septa release method was developed to selectively identify, target and manually release the tethers in a precise manner from a single insertion point (Revelle Aesthetics). The following pilot study evaluated the safety and feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…As demonstrated herein and in the published 3-month data, the CONFFIRM trial demonstrated statistically significant, durable improvement in reducing the appearance of cellulite with a powered multi-center pivotal study, confirming the safety, efficacy, and feasibility of the procedure demonstrated in 2 pilot studies of the device. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As demonstrated herein and in the published 3-month data, the CONFFIRM trial demonstrated statistically significant, durable improvement in reducing the appearance of cellulite with a powered multi-center pivotal study, confirming the safety, efficacy, and feasibility of the procedure demonstrated in 2 pilot studies of the device. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated herein and in the published 3-month data, the CONFFIRM trial demonstrated statistically significant, durable improvement in reducing the appearance of cellulite with a powered multi-center pivotal study, confirming the safety, efficacy, and feasibility of the procedure demonstrated in 2 pilot studies of the device. 20,21 The device for TVS is unique in that it provides tactile and visual feedback, allowing for the assessment of the contribution of septal fibers engaged by the deployable hook to an individual depression before the blade is employed to release the septa. It is already well established the role of fibrous bands in of cellulite and this study confirms the importance of targeting the bands which create the depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The newest technology in manual subcision is a controlled focal septa release method (Avéli; Revelle Aesthetics, Inc, Mountain View, CA) that has been shown to be effective for cellulite in the buttocks and thighs. 7,8 This technique has also been associated with ecchymosis, as shown in a study of 20 women, in whom this AE persisted for a mean duration of 17.6 days after treatment. AEs that were reported in $10% of treated women included ecchymosis (100%); edema (45%); soreness, pain, or tenderness (45%); and nodules (10%).…”
Section: Subcision Treatments' Sequelaementioning
confidence: 92%
“…The newest minimally invasive subcision method—controlled focal septa release—can selectively identify, target, and manually release tethers with precision (Avéli; Revelle Aesthetics, Inc., Mountain View, CA). 10 This device enables visualization of target septa on the skin, and multiple depression sites can be treated from a single insertion site. After anesthesia, the device is inserted through the skin and advanced to a depression site guided by a light indicating the end of the device under the skin.…”
Section: Current Treatments and Technologiesmentioning
confidence: 99%